feruza THE ROLE OF INDIVIDUAL WORK IN FOREIGN LANGUAGE LESSONS: THE ROLE OF INDIVIDUAL WORK IN FOREIGN LANGUAGE LESSONS - Hiloliddinova, Feruza (Журнал иностранных языков и лингвистики, 2022)
This article introduces students to the knowledge, abilities, beliefs and spirituality of practical classes from teacher to student, but only touches on words. This process tests familiarity, perception, individual processing, understanding of these abilities and concepts.